Fatigue Analysis of 5000 GT Ferry Ro-Ro’s Car Deck Using Finite Element Method - Wulandari, Amalia Ika; Rahmasari, Nindy widia Devi; Adnyani, Luh Putri; ,, Alamsyah; Ikhwani, Rodlian Jamal (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2021)
Ro-Ro Passenger Ship type crossing ship is a ship that is operated to connect 2 (two) ports. On the Ro-Ro ship there is a car deck as one of the vital construction structures, because it is used to support the vehicle load on it. This study aims to determine the value of fatigue life in car deck construction by reviewing hot spot stress areas that are prone to cracking. The value of the fatigue analysis is taken from the greatest stress value and the shortest cycle is taken at each plate thickness variation. The method used is the finite element method (FEM) by varying the thickness of the car deck plate assisted by using finite element based software. The results showed the highest maximum stress was found on car deck 1 with a thickness of 80% (9.6 mm) which was 241.16 Mpa, while the lowest minimum stress was found on car deck 2 with a thickness of 110% (13 mm) which was 103.07 Mpa. The highest value of fatigue life is found in car deck 2 with a plate thickness of 110% (13 mm) of 74.23 years with a stress cycle of 1350000 times, while the lowest fatigue life value is found in car deck 1 with a plate thickness of 80% (9.6 mm) of 7.63 years with a voltage cycle of 220000 times